2001
DOI: 10.1103/physrevlett.86.1255
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Boson Peak in Systems with Lattice Disorder

Abstract: The origin of the boson peak in models with force-constant disorder has been established by calculations using the coherent potential approximation. The analytical results obtained are supported by precise numerical solutions. The boson peak in the disordered system is associated with the lowest van Hove singularity in the spectrum of the reference crystalline system, pushed down in frequency by disorder-induced level-repelling and hybridization effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
336
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(365 citation statements)
references
References 19 publications
24
336
2
3
Order By: Relevance
“…This peak is located at an almost constant energy, in an energy region typical of the boson peak (BP), as it will be also shown from the more detailed analysis. The comparison with experimental results on other systems and with moleculardynamics simulations 7,8,23 suggests the interpretation of this low-frequency feature as the high-frequency evolution of the transverse-acoustic mode. 25 However, it should be noted that the density fluctuation modes loose their symmetry as the wave vector is increased, so that the longitudinal and transverse terms have not a well defined significance.…”
Section: Methodsmentioning
confidence: 83%
“…This peak is located at an almost constant energy, in an energy region typical of the boson peak (BP), as it will be also shown from the more detailed analysis. The comparison with experimental results on other systems and with moleculardynamics simulations 7,8,23 suggests the interpretation of this low-frequency feature as the high-frequency evolution of the transverse-acoustic mode. 25 However, it should be noted that the density fluctuation modes loose their symmetry as the wave vector is increased, so that the longitudinal and transverse terms have not a well defined significance.…”
Section: Methodsmentioning
confidence: 83%
“…[13][14][15][16] Figure 8 presents the reduced low-frequency Raman spectra of KMWPO and RbMWPO glasses in two different reduction schemes:…”
Section: E Low-frequency Raman Scattering: Boson Peakmentioning
confidence: 99%
“…The first technique gives information about short-range structure of glasses and allows studying the so-called "Boson peak." [12][13][14][15][16] Study of the Boson peak is of great interest since its origin still remains unclear. [13][14][15][16] On the other hand, heat capacity studies may provide, among others, some information on fragility, structural relaxation, and aging effects in glasses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on harmonic lattice models demonstrated that softening of disordered force constants can smear and push to low frequencies peaks which exist in the crystalline DOS [10,11,12]. In another approach the vibrations of a random distribution of atoms, interacting with a Gaussian-shaped pair potential, was studied [13] in a harmonic scalar approximation.…”
Section: Introductionmentioning
confidence: 99%